Peran KH. Ahmad Dumyati Dalam Keagamaan Di Desa Seribandung Tahun 1960-1996 M - Ramadhan Ramadhan; Fitriah Fitriah (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
This study describes the role of KH. Ahmad Dumyati in Religious Social Life in Seribandung Village, Ogan Ilir Regency in 1379-1416 H/1960-1996 M. KH. Ahmad Dumyati is the second mudir at the Pondok Pesantren Nurul Islam Seriandung. Apart from a mudir KH. Ahmad Dumyati is a religious figure from Seribandung Village, he is a kiai who is active in preaching using the cawisan method. KH. Ahmad Dumyati is a preacher and is also active in organizational careers, both educational and political organizations. KH. Ahmad Dumyati himself was appointed a member of the DPRD / TK I South Sumatra in 1971.